THU0663 Rheumatology adolescent and young adult care: real world challenges and opportunities. (12th June 2018) - Malaiya, R.; Steer, S.; Das, S.; Mathews, C.; Davies, U.; Godbold, E.; Lamb, S.; Vale, S.; Goncalves, V.; Sumbwanyambe, M.; Sumbwanyambe, M.; Thurlbeck, S.; et al.
Abstract : Background: Adolescents and young adults (AYA) form one sixth of the world's population and account for 6% of the world's global burden of disease. Those with chronic illness are particularly vulnerable. Globally, significant improvements in healthcare related morbidity and mortality have been seen, but not within the 10–24 year old group. Adolescence is a rapidly changing, formative phase of human development; opportunities exist to impact this through restructing care pathways and patient empowerment. Objectives: Establish awareness of current national guidance and identify unmet needs in existing rheumatology AYA systems. Methods: Interested parties from South East England (South London, Kent, Surrey and Sussex) formed a multi-disciplinary, patient based, co-design initiative (RAYA collaborative) which included representatives from primary/secondary/tertiary care, allied health professionals and a youth worker/patient from the charity sector. Our discussions and an anonymous survey to hospitals in the region, formed the basis of a qualitative and quantitative analysis, which helped gain a holistic insight into the challenges and opportunities in delivering AYA care in our region. Results: 15/20 centres, covering an 8 million population, responded; 4 tertiary care hospitals, 11 district general hospitals with 32 responses (19 consultants, 13 senior registrars). 31 (97%) of responders felt that AYA cohort (16–25 years old) required an approach different to that of older adults. 25 (78%) felt there was a need for dedicated AYA services. 23 (72%) and 17 (53%) were aware of UK national guidelines CQC 2014/ NICE NG43 2016 respectively) for transitional/integrated and coordinated care. Barriers to developing dedicated AYA services (% of responders): Not a priority for NHS managers, 31 other clinical priorities, 31 insufficient patient numbers, 22 not cost effective, 19 unlikely to be commissioned, 19 more research required, 13 cohort by diagnosis, 13 other ways to deliver care, 13 only focus on transitioning patients from paediatrics 13 Responders would like assistance in future care delivery through: Clinical toolkit: 63% n=20, Service commissioning toolkit: 43% n=14, Training: 43% n=14, Workshops: 47% n=15. Potential low cost/cost neutral approaches to systems change, cultural change, education and sharing of resource were discussed (see image). Conclusions: Improving outcomes for AYA patients through delivering age appropriate care and self advocacy has driven global strategy and guidelines. Our survey identifies that the majority of rheumatologists agree with this, however there is room for improvement regarding awareness and implementation of current guidance. Financial constraints and whole population healthcare delivery has limited change. A systematic, unified approach within regions may help to effect change. There is a demand for the development of clinical and commissioning toolkits and training/workshops to help facilitate this. Reference: [1] Global Accelerated Act on for the Health of Adolescents WHO2017. Disclosure of Interest: None declared